학술지 <미디어와 인격권> 10년의 연구동향과 학문적 영향력 - 김민정; Kim Minjeong (미디어와 인격권, 2025)
본 연구는 학술지 <미디어와 인격권>의 지난 10년간 연구동향과 학문적 영향력을 분석하여 해당 학술지가 언론법 연구에 기여한 바를 조명하는 것을 목적으로 한다. 연구대상은 2015년 창간 이후 2024년까지 게재된 총 102편의 논문이며, 연구방법으로는 문헌계량학(bibliometrics)과 내용분석(content analysis)을 활용하였다. 분석 결과, 명예훼손·모욕·혐오표현(15.7%), 프라이버시(14.7%), 신기술 연계 복합 주제(11.8%), 미디어규제법(10.8%) 등이 가장 많이 연구된 주제였으며, 이는 디지털 환경 변화에 따른 법적 이슈가 지속적으로 학문적 관심을 받아왔음을 시사한다. 연구방법으로는 법해석학적 접근(법 규정 중심, 판례 중심, 법 규정+판례분석)이 65% 이상 차지하여 법리적 분석이 주된 연구 방식임을 확인하였다. 아울러, 연구자의 전문 분야(언론학 vs. 법학)에 따라 연구주제 및 연구방법 선택에 유의미한 차이가 있었다. 언론학 연구자들은 미디어 규제법 주제 및 양적연구방법을, 법학 연구자들은 프라이버시, 신기술 관련 주제 및 법해석학적 연구방법을 보다 선호하는 경향을 보였다. 연구 협업을 보면, 공동연구 비율이 13.7%에 불과하고 법학자-언론학자의 공동연구 사례가 전무한 것으로 나타났다. 인용을 토대로 학문적 영향력을 파악한 결과, <미디어와 인격권>은 신문방송학과 법학 분야의 대표 학술지들과 긴밀한 인용관계를 유지하고 있으며, 법학과 언론학의 융합 연구에 중요한 기여를 하고 있음을 확인하였다. 다만 학술지 영향력지수(Impact Factor: IF)가 최근 하락했고 <미디어와 인격권>의 자기 인용비율이 높다는 점은 연구 확산 범위가 제한적일 가능성을 시사한다. 학술지의 향후 발전 방향으로는 법사회학적 접근 확대, 학제 간 협업 강화, 디지털 시대의 법적 쟁점 연구 심화, 학술적 영향력 확대 노력 등을 제안한다. This study aims to analyze the research trends and academic impact of the Journal of Media and Defamation Law over the past decade, shedding light on its evolving contributions to media law scholarship in South Korea. Since its launch in 2015, the journal has become a key platform for academic discussion on legal issues surrounding media practices. The study examines a total of 102 articles published in the journal from 2015 to 2024 and employs bibliometric analysis and content analysis as the primary research methods. The findings reveal that the most frequently studied topics include defamation, insult, and hate speech (15.7%); privacy (14.7%); multiple domain legal issues related to new technologies such as artificial intelligence (AI) and digital platforms (11.8%); and media regulation laws (10.8%). These results suggest that legal issues arising from digital transformations continue to attract academic interest. From a methodological perspective, over 65% of the analyzed studies relied on a legal interpretative approach, focusing on statutory analysis and judicial precedents. Meanwhile, a notable disciplinary distinction was observed in research preferences: media and communication scholars tend to favor media regulation topics and quantitative methodologies, while legal scholars focused more on privacy, technology-related issues, and legal interpretation. The analysis also revealed a low level of interdisciplinary collaboration. Only 13.7% of the studies were co-authored, and there were no instances of joint research between legal and media scholars. This suggests a critical lack of interdisciplinary engagement, which may limit the journal’s potential to bridge the divide between legal theory and media practice. An analysis of the journal’s academic impact shows that Journal of Media and Defamation Law maintains strong citation linkages with leading journals in both journalism and law, thereby confirming its crucial role in fostering interdisciplinary legal studies. However, the journal's impact factor has declined recently, and its high self-citation rate suggests limitations in the scope of its research dissemination. Moving forward, efforts should focus on expanding socio-legal approaches, strengthening interdisciplinary collaboration, deepening research on legal challenges in the digital era, and enhancing the journal’s academic impact to further advance the field of media law research. Such efforts are essential in strengthening the journal’s relevance and advancing the field of media law in an increasingly complex information society.